Creation of mental model for staging during murders concealment - В. В. Семеногов (Теорія і практика правознавства, 2016)
Problem setting. In theory, criminology also still remain undeveloped important provisions relating to methods of investigating murders staged hidden. The latter include methods of staging and detection of negative circumstances as the results of the study of causal relationships in the inspection of the site and kinds og staging investigation. The complexity of the investigation of these crimes is not only that the investigator has a limited amount of evidence-based information, and the fact that some of it given in the form of perverted that prevents proper construction of investigative leads and determine the direction of the investigation. Recent research and publications analysis:An important contribution to the study of theoretical problems associated with investigating murders, including those hidden staged, forensic scientists have made Ukraine and other countries. Problematic issues considered in the investigation of murders studies T.V. Averyanova, V.P. Bahina, R.S. Belkin, V.I. Boyarov, O.U. Bululukov, I.V. Borisenko, V.A. Guravel , A.V. Ishchenko, V.O. Konovalova, V.S. Kuzmichev, V.G. Lukashevich, V.V. Tishchenko, V.U. Shepitko, M.P. Yablokov et al. Paper objective: The purpose of this article is detailed review of steps of forming an imaginary models of staging at concealing murder, focused attention on the importance of reflective thinking as the basis of mental activity and criminal thorough analysis of certain types instsenuvan, in particular, the nature of staged events and the complexity affecting the pattern of thinking perpetrator . Paper main body: The article stated that the staging has particular difficulty in imaginary models construction that is the basis for future action to implement it. The difficulty lies in the whole chain of reasoning logically belonging to methods of staging and reflective thinking that is playing a mentally investigator and surrounding persons involved in the investigation. Mental activity offender, based on reflective thinking, makes staging process into three stages: a) imaginary staging - forming in the mind of the subject representations about the situation, he wants to create, to mask the crime; b) implementation plan, implement it into practice in the form of staging; c) Preparation of reasoning that explains the facts established investigators. Conclusions of the research: Therefore, it can be noted that the thinking of the parties is subject to the special rules that are in the plans, actions, behavior stakeholders, and marked a kind of logical structure of intellectual interaction between these parties. Its nature is full or partial synchronization considerations rivals mutual simulate these considerations and opportunities reflexive control actions of the other.